Numerical Evaluation of Slender Glass Panel with Complex Geometry Subjected to Static Load and Soft-body Impact - Kozłowski, Marcin (Periodica Polytechnica Civil Engineering, 2021)
Current standards and glass codes of design practice require that glazing used in architectural applications has to be resistant to, in addition to typical loads, also accidental events, in particular human impact, without showing damage that is disproportionate to the original cause. A case study was performed of an indoor glass lantern in a public building made from slender two-side supported glass panels with a complex geometry (36 ventilation holes). The paper provides structural assessments and results of in-situ experiments including static loading and soft body impact. Results from numerical simulations of impact loading on the glass panels complementing the experimental results are also presented.